2017
DOI: 10.5539/ies.v10n12p130
|View full text |Cite
|
Sign up to set email alerts
|

On The Relationship between Listening and Speaking Grades of AL-Balqa Applied University English as a Foreign Language Students

Abstract: This paper aims at exploring the relation between the two skills of listening and speaking. In addition, it tries to investigate the presence of any gender differences in this relation. To achieve these ends, the listening and speaking exams marks of (122) EFL students registered in the English 102 on-line compulsory course were analyzed using SPSS. The findings proved the existence of a positive relation between the two skills (r=0.433). The Independent Sample T-Test also proved that there were significant st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Rankin [13] indicated that listening is the most frequently used language activity and has a close relationship with speaking skills. According to the study of Abu-Snoubar [14] listening has an influence on the development of oral proficiency in EFL classes. To help EFL learners improve their listening and speaking skills, researchers investigated the impacts of different factors.…”
Section: Discussionmentioning
confidence: 99%
“…Rankin [13] indicated that listening is the most frequently used language activity and has a close relationship with speaking skills. According to the study of Abu-Snoubar [14] listening has an influence on the development of oral proficiency in EFL classes. To help EFL learners improve their listening and speaking skills, researchers investigated the impacts of different factors.…”
Section: Discussionmentioning
confidence: 99%
“…From activities that involving listening skill, such as listening to audiobooks or dramas, English-language podcasts or English-language songs, students can be familiar and understand when people communicating by using English. There is strong positive relation between listening and speaking Snoubar (2017). The more often they listen English language, they will become familiar with it.…”
Section: B Discussionmentioning
confidence: 99%
“…Limited research exists investigating how listening correlates to speaking by adopting an experimental research design that implements a particular teaching strategy or technique. Some researchers correlated the students' listening and speaking scores and reported that they were correlated positively (Abu-Snoubar, 2017;Demir, 2017;Hoang & Ngoc, 2021).…”
Section: Theoretical Reviewmentioning
confidence: 99%